Mindfulness as a Protective Factor for the Burden of Caregivers of Amyotrophic Lateral Sclerosis Patients. Issue 1 (20th October 2015) - Pagnini, Francesco; Phillips, Deborah; Bosma, Colin M.; Reece, Andrew; Langer, Ellen
Abstract : Objectives: Caregivers of people with severe chronic conditions, such as amyotrophic lateral sclerosis (ALS), are at risk of developing depression and anxiety and reduced quality of life. Few studies have explored protective factors in this population and none investigated the role of mindfulness. The study aimed to examine the relationship between mindfulness and health‐related outcomes in a population of ALS caregivers. Methods: We conducted an online survey with ALS caregivers, and again at 4‐month follow‐up, to assess mindfulness, burden, quality of life, anxiety, and depression. The associations between mindfulness and the other outcomes were evaluated both cross‐sectionally and longitudinally. Results: Mindfulness correlated negatively with burden, depression, and anxiety and positively with quality of life, maintaining stability through time. Conclusion: Our results showed that mindfulness is positively related to quality of life and negatively related to level of burden. We suggest that this construct can represent a preventative factor toward the negative effects of caregiving.